Francoski pogled na slovensko-srbske spore leta 1989 - Mujdrica, Kaja (Studia Historica Slovenica, 2024)
Based on an analysis of material from the French diplomatic archives of the Ministry of Europe and Foreign Affairs in Nantes and La Courneuve, as well as the French newspapers Le Monde and Le Figaro, this article examines the French perspective on Slovenian-Serbian political relations in 1989. The authors focus on three key events: the assembly in Cankarjev dom on 27 February, the adoption of the amendments to the Slovenian constitution on 27 September and the failed "Rally of Truth" in Ljubljana on 1 December. They paid particular attention to aspects of the reporting by diplomats from the French Embassy in Belgrade.
Keywords: amendments to Slovenian constitution; diplomacija; diplomacy; France; Francija; Jugoslavija; mitingaški pohodi; Serbia; Slovene-Serbian conflicts; Slovenia; Slovenija; slovensko-srbska nasprotja; Srbija; ustavna dopolnila; Yugoslavia